2015
DOI: 10.7745/kjssf.2015.48.5.332
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study of Different Biochars as Adsorbent for Cadmium and Lead

Abstract: The objective of this study was to evaluate the effectiveness of different biochars on the removal of heavy metals from aqueous media. The experiment was carried out in aqueous solutions containing 200 mg CdL -1 or 200 mg PbL -1 using two different biochars derived from soybean stover and orange peel (20 mg Cd or Pbg -1 biochar). After shaking for 24 hours, biochars were filtered out, and Cd and Pb in the filtrate were analyzed by flame atomic absorption spectrophotometer (FAAS). In order to provide informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Sequential extraction procedures, such as BCR, have been used to operationally define soil metal pools in various settings (Guerra et al, 2007; Ippolito et al, 2009; Nemati et al, 2009), including under biochar application (Houben and Sonnet, 2015; Kim et al, 2015; Zhu et al, 2015). As stated by Houben and Sonnet (2015), sequential extraction procedures suffer from a lack of selectivity and element redistribution during extraction, yet their use is justified when the goal is to compare differences in a soil as affected by different treatments, as in the current study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequential extraction procedures, such as BCR, have been used to operationally define soil metal pools in various settings (Guerra et al, 2007; Ippolito et al, 2009; Nemati et al, 2009), including under biochar application (Houben and Sonnet, 2015; Kim et al, 2015; Zhu et al, 2015). As stated by Houben and Sonnet (2015), sequential extraction procedures suffer from a lack of selectivity and element redistribution during extraction, yet their use is justified when the goal is to compare differences in a soil as affected by different treatments, as in the current study.…”
Section: Resultsmentioning
confidence: 99%
“…Their results showed that metal sorption was mainly due to precipitation with carbonate or phosphate species, with less sorption due to surface complexation or π electron bonding. Kim et al (2015) used soybean [ Glycine max (L.) Merr.] stover and orange ( Citrus x sinensis ) peel biochars to remove aqueous Cd and Pb.…”
mentioning
confidence: 99%
“…Biochar, a carbon-rich byproduct derived from biomass pyrolysis under oxygenlimited conditions (Wang et al 2016), shows significant promise as a heavy metal sorbent (Mohan et al 2014;Kim et al 2015;Ippolito et al 2017). Ippolito et al (2017) found that pine biochar can reduce bioavailable soil metals (Cd, Cu, Pb, and Zn), which were extracted with 0.01 M CaCl2.…”
Section: Introductionmentioning
confidence: 99%